ANALISIS POTENSI BAHAYA DAN KECELAKAAN KERJA PADA PT. XYZ MENGGUNAKAN METODE HAZARD AND OPERABILITY STUDY (HAZOP) - Andree Shevchenko (2023)
PT. XYZ is a business that operates independently in the remote sector which is inseparable from occupationalihealthiandisafety issues. Occupationalmsafetymandmhealth is aifieldirelatedito health, safety and human welfare that cannot be separated from the production process. Thisiresearchiwasiconducted to determine the potential hazards (hazards) thatmcanmthreaten the safety of workers to result in work safety. Accidentmpreventionmcan be done by analyzing every hazard in the work environment using the HAZOP (Hazard and Operability Study) method. The HAZOPimethod is a risk identification technique that occurs in a job. Frommthemresults of the study there are several potential hazards from work carried out by workers. Toireduceitheipotential risk of danger, a system for improving work attitudes, regulations and policies is designed formworkers in using personalmprotective equipment and supervising workersmwhomviolate work safety regulations so as to prevent work accidents for workers.